Students' Learning Interest in the Pancasila Course During the COVID-19 Pandemic: A Study of Chemical Analysis Students at Polytechnic of AKA Bogor - Heru Subakti Dwiko Laksono; Nunung Widijantie; Ahmad Syarkini; Nur Indah Riswati; Moh Hayat (Journal of General Education and Humanities, 2026)
The COVID-19 pandemic has affected various sectors, including education. During the pandemic, teaching and learning activities have often encountered challenges. One of the major challenges higher education institutions faced was maintaining students’ interest and engagement in learning during the transition to online learning. This study was designed to determine students' learning interest in the Pancasila course in the Chemical Analysis Study Program at the Polytechnic of AKA Bogor. The research was conducted from June to November 2022. The sample for this research consisted of 2nd-semester students in the 2021/2022 academic year. The research method used was descriptive quantitative research. This study uses primary data. To obtain data, the author distributed questionnaires to respondents who had completed Pancasila Courses, and the results were then analysed. Data were analysed using percentage calculations and categorised according to predetermined interpretation criteria. The interest in the Pancasila course among students of the Chemical Analysis Study Program at the Polytechnic of AKA Bogor is 41–60%, placing it in the ‘less’ category. These findings indicate that students’ affective, behavioural, and cognitive engagement in the Pancasila course has not yet reached an optimal level. Therefore, improvements in instructional strategies are necessary to enhance students’ interest in learning and overall learning outcomes.